2015
DOI: 10.1136/annrheumdis-2015-eular.1159
|View full text |Cite
|
Sign up to set email alerts
|

SAT0423 Understanding Delay in Diagnosis, Access to Care and Satisfaction with Care in Lupus: Findings from a Cross-Sectional Online Survey in the United States

Abstract: BackgroundEarly diagnosis is an area of great unmet need in lupus. This need and other aspects of care have been reported from a provider's perspective.ObjectivesThe aims of this survey were to understand the experience of patients with diagnostic delays and to assess their access to care and the extent to which their care needs are met.MethodsAn online cross-sectional survey of English-speaking respondents aged ≥18 years with self-reported diagnosis of lupus was conducted across the US in partnership with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Our data show a median delay of 47 months from the first SLE symptom to the diagnosis of SLE, comparable with the reported data of an US-cohort of 827 patients from Sawah et al. 3 Interestingly, the time to diagnosis in both cohorts was mainly due to the time between the first physician’s visit and diagnosis (34 ± 61.7 in our cohort vs. 41 ± 64.8 months in the cohort of Sawah et al.). In both countries, the mean time from the onset of symptoms to the first physician’s visit (13 months in our cohort versus 25 months in the US-cohort) was significantly lower compared to the time between the first physician’s visit and diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data show a median delay of 47 months from the first SLE symptom to the diagnosis of SLE, comparable with the reported data of an US-cohort of 827 patients from Sawah et al. 3 Interestingly, the time to diagnosis in both cohorts was mainly due to the time between the first physician’s visit and diagnosis (34 ± 61.7 in our cohort vs. 41 ± 64.8 months in the cohort of Sawah et al.). In both countries, the mean time from the onset of symptoms to the first physician’s visit (13 months in our cohort versus 25 months in the US-cohort) was significantly lower compared to the time between the first physician’s visit and diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“… 18 Thus a delayed diagnosis, the uncertainty caused by a delayed diagnosis and the resulting delay in therapy may be of importance. 3 Therefore, we analysed the impact of a delayed diagnosis on long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the third year before diagnosis as a reference, to avoid distortion by the higher expected costs in the 24 months preceeding formal SLE diagnosis. Specifically, previous research has demonstrated that patients present with symptoms that might not be recognized immediately; for example, Al Sawah et al [ 35 ] reported an average of 2.1 years between first lupus symptoms and seeking of medical care. We then used a random-effects (random intercepts) model to estimate patient-specific annual trends in mean all-cause health-care costs, adjusting for age and disease severity.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical manifestations are heterogeneous with varying disease severities, organ involvement, and cellular abnormalities (4,5). The clinical course is unpredictable, with frequent flares, which contributes to both delayed diagnosis (an estimated six years after initial presentation) (6) and difficulties in treatment. Circulating immune complexes, consisting of autoantibodies and endogenous antigen, are deposited in tissues leading to inflammation and end-stage organ damage.…”
Section: Introductionmentioning
confidence: 99%